MOTIF KHALAYAK DALAM MENGAKSES BERITA BENCANA HIDROMETEOROLOGI DI INSTAGRAM @INFOSUMBAR SEBAGAI MEDIA ALTERNATIF BERBASIS PARTICIPATORY JOURNALISM - Chairunnisa; Besman, Abie; Sri Mulyani, Henny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The need for fast and accurate information in crisis situations has transformed public news consumption patterns, especially with the presence of participatory journalism on social media. Instagram @infosumbar plays an important role as an alternative media based on participatory journalism that presents disaster news in West Sumatra by utilizing citizen participation. This study aims to identify audience motives in accessing news about hydrometeorological disasters in West Sumatra in November-December 2025 on Instagram @infosumbar using the uses and gratifications 2.0 MAIN Model theory by Sundar & Limperos (2013). The research method used is a descriptive quantitative survey with a purposive sampling technique to 384 respondents. The results show that agency motives are the main driver (88%), reflecting public empowerment in disseminating information, a strong sense of ownership and building a community on @infosumbar during the disaster crisis. Modality motives are in second place (86.2%), driven by public trust in the visualization of amateur video content from citizens that feels more real and like being at the scene. Furthermore, navigability (84.9%) facilitates easy access to structured disaster information, and interactivity (81%) is the most important factor, providing a responsive two-way communication with the media and other audiences. The dominance of agency demonstrates @infosumbar's success as an alternative media platform that implements participatory journalism. Infosumbar transforms social media into a disaster mitigation infrastructure by strengthening community networks and active audience engagement during emergency situations.